INFECTION BY HOOKWORMS IN AN INDIGENOUS REMOTE REGION OF THE LEGAL AMAZON, BRAZIL - Francisco Malheiros, Antonio (2014)
Hookworms infection has become an increasingly serious threat to public health in Brazilian indigenous. Detection and/or clinical cases of hookworms have been reported in the past; however, nothing is known about the prevalence among indigenous Tapirapé in Brazil. We studied the presence of hookworms in indigenous Tapirapé ethnic group from county of Confresa, State of Mato Grosso, Brazil. Stool samples were collected from 542 members of the Tapirapé ethnic group and analyzed using formalin-ethyl ether and formalin-ethyl acetate sedimentation, and zinc sulfate flotation. Hookworms were detected in 104 (19.24%) indigenous and the prevalence was similar in males (21.29%) and females (17.20%). Males aged under 16 years were more frequently infected. Symptoms such as diarrhea and abdominal pains were reported from 104 infected individuals . Other symptoms associated with hookworms infection were vomiting, cramps and weight loss. No significant association with diarrhea was noted in individuals infected with hookworms. Hookworms are frequent intestinal parasites in Tapirape indians and the results suggest a high level of environmental contamination.